Analisis Faktor-Faktor yang Berpengaruh terhadap Minat Pengguna E-Filling: studi terhadap Wajib Pajak di KPP Makassar Selatan - IRMA ADCHANIA CHALIK (STIM LASHARAN JAYA MAKASSAR, 2017)
Analysis of factors influencing the interest in the use of e-filing facilities at KPP Pratama Makassar Selatan (supervised by Mursalim and Darwis Lannai). The aims of this research are: a) To know the effect of Perception of Utility to Taxpayers interest in using e-filing facility; b) To know the influence of perception of ease of interest of taxpayer in using e-filing facility; c) To know influence of Perception of complexity to interest of Taxpayers in using e-filing facility; d) To know influence Perception of technology mastery to Taxpayer interest in using e-filing facility. The analysis used multiple linear regression method through a questionnaire on 88 corporate taxpayers from the total 743 corporate taxpayers who using e-filing until July 2017 in KPP Pratama Makassar Selatan. The result of the research shows usability perception (X1) has a positive and significant effect on the taxpayers’interest in the use of e-filing. This is with a significance level of 0.006 with a coefficient value of 0,117 or 11,7%. These findings can make the use of e-filing will cause the higher the mandatory pay by using e-filing . Convenience perception (X2) had significant value 0,0000 with coefficient value 0,185 or 18,5%. This finding make the easier to use e-filing,the higher the interest of corporate taxpayers to report the annual tax return. Complexity perception (X3) had positive effect with the significant value of 0,025 and the regression valuef of 0,086 or 8,6%. This of course makes a technology hence will reduce the interest oin using e-filing. However, the effect of the complexity in this study is very small. Technological mastery (X4), psotive and significant influence on taxpayers interest in using e-filing as a media of reporting the annual tax return.It is withregression value of 0,138 or 13,8% with asignifivaance level of 0,038. This has brought technological progress to become part of the needs of modern society in terms of communicating from all sides , including business, financial, fiscal, and other infringing needs. With the results of the more sophisticated technology, and the increasingly mastered information technology, it will further encourage the taxpayers interest in using it.